Analysis of Dowry Laws in The State of Sarawak, Malaysia, and KHI Indonesia - Ridho Syahbibi (Indonesian Journal of Law and Islamic Law (IJLIL), 2022)
The law of dowry in Islam is an obligation for a man who wants to marry his future wife. Article 30 of the Compilation of Islamic Law (KHI) in Indonesia explains that the prospective groom is obliged to pay a dowry to the prospective bride in an agreed amount, both in form and type. However, there is no certainty about the amount of dowry to be paid. Another Muslim-majority country that adheres to Islamic law in the context of family law, including dowry, is Malaysia, which has the Sarawak State Islamic Family Law Ordinance 2001 which also regulates dowry laws. Thus, in solving a problem related to the amount of the dowry, the judge will solve it. This study uses a type of library research with a juridical-normative method. Primary data sources in the form of laws and regulations regarding the law of dowry in Indonesia and Malaysia, secondary sources obtained from various writings and books that are relevant to the research focus. Result: in detail the dowry law in the preparation of Islamic law is regulated in Articles 30 to 39, while the 2001 Sarawak State Islamic family law procedures in Malaysia are contained in Article 19, Article 56 and Article 57. Both have similarities in the laws and regulations that discuss about the law. dowry, one of the most prominent differences between the two is regarding the determination of the dowry, which in Indonesia the dowry is not clearly defined in terms of form and amount, while in the State of Sarawak, Malaysia, the amount is 120 RM for virgins and widows.